Qur’an for Android; Sebuah Upaya Kontemporer Pemeliharaan al-Qur’an oleh Para Sukarelawan - Syarif Hidayat (SALIHA: Jurnal Pendidikan & Agama Islam, 2021)
This article will discuss about what is the Quran for Android, what is the purpose of the Quran for Android being developed by volunteers and how the volunteers develop the Qur'an for Android in an effort to preserve the Qur'an. The object of research in this study is the Quran for Android application. Data collection techniques are used to collect information related to the required data using observation and documentation techniques. After the required data has been collected, then a descriptive qualitative analysis is carried out. The results showed that the Quran for Android application is a Reference Book category application for all ages with the main content being the Koran and its supporting materials developed by a community of volunteers who are aware of the Quran, distributed open source within the Android operating system and can be used for free by users via downloads on the PlayStore. The goal that the developers want to achieve is to make the Koran easier to learn, teach, read, understand, memorize, listen to, analyze by Muslims considering the Koran as a guide for life and this application is developed without any purpose of profit oriented at all, all dedicated to the Noble Koran and done totally lillahita'ala. The Quran for Android application was developed using the Android Studio authoring tool software, with the dominance of the Ruby programming language, developed by a community that has a concern for the maintenance of the Koran which is incorporated in a social network system specifically designed for developers, namely GitHub which allows volunteers to complete issues found and added features worth adding.